Dysmenorrhea Management Education and Knowledge Improvement Among Indonesian Adolescent Girls: Edukasi Manajemen Dismenore dan Peningkatan Pengetahuan pada Remaja Putri di Indonesia - Sherllia Sofyana (Journal of Current Health Sciences, 2026)
Background: Dysmenorrhea is a common health problem among adolescent girls and may interfere with comfort, concentration, school attendance, and daily activities. Limited knowledge about menstrual pain management can lead adolescents to normalize pain and use inappropriate strategies. This study aimed to analyze differences in knowledge levels before and after health education on menstrual pain management among adolescent girls at Senior High School 3 Palu. Methods: This quantitative study used a pre-experimental one-group pretest–posttest design. Thirty-six female students who experienced menstrual pain and met the inclusion criteria were recruited using total sampling. Health education was delivered in groups using a structured lesson plan and leaflet. Knowledge was measured using a 15-item true–false questionnaire before and after the intervention. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and the Wilcoxon Signed-Rank Test. Results: Before health education, most respondents had poor knowledge (77.8%), while 22.2% had fair knowledge. After the intervention, 91.7% of respondents had good knowledge and 8.3% had fair knowledge. The Wilcoxon test showed a significant increase in knowledge (Z = -5.20; p < 0.001), with a large effect size (r = 0.87). Conclusion: Health education was associated with improved knowledge of menstrual pain management among Indonesian adolescent schoolgirls. ABSTRAK: Latar Belakang: Dismenore merupakan masalah kesehatan yang umum dialami remaja putri dan dapat mengganggu kenyamanan, konsentrasi, kehadiran di sekolah, serta aktivitas sehari-hari. Keterbatasan pengetahuan tentang manajemen nyeri menstruasi dapat membuat remaja menganggap nyeri sebagai kondisi biasa dan menggunakan strategi penanganan yang kurang tepat. Penelitian ini bertujuan untuk menganalisis perbedaan tingkat pengetahuan sebelum dan sesudah pendidikan kesehatan tentang manajemen nyeri menstruasi pada remaja putri di SMA 3 Palu. Metode: Penelitian kuantitatif ini menggunakan desain pre-experimental one-group pretest–posttest. Sebanyak 36 siswi yang mengalami nyeri menstruasi dan memenuhi kriteria inklusi direkrut menggunakan teknik total sampling. Pendidikan kesehatan diberikan secara kelompok menggunakan satuan acara penyuluhan dan leaflet. Pengetahuan diukur menggunakan kuesioner benar-salah sebanyak 15 item sebelum dan sesudah intervensi. Data dianalisis menggunakan statistik deskriptif, uji normalitas Shapiro–Wilk, dan Wilcoxon Signed-Rank Test. Hasil: Sebelum pendidikan kesehatan, sebagian besar responden memiliki pengetahuan kurang (77,8%), sedangkan 22,2% memiliki pengetahuan cukup. Setelah intervensi, 91,7% responden memiliki pengetahuan baik dan 8,3% memiliki pengetahuan cukup. Uji Wilcoxon menunjukkan peningkatan pengetahuan yang signifikan (Z = -5,20; p < 0,001), dengan ukuran efek yang besar (r = 0,87). Kesimpulan: Pendidikan kesehatan berkaitan dengan peningkatan pengetahuan tentang manajemen nyeri menstruasi pada remaja putri sekolah di Indonesia.